Sejarah Munculnya HarA ̅Kat Dalam Tulisan Arab - Huwaina Rabithah Nur; Salwa Haifa; Fadhla Abi Hidayah; Kiki Haura Shandi; Ariza Amalia; Sahkholid Nasution (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Language is a tool used to communicate. In Arabic there is a sign known as Harakat. The purpose of the research is to find out how the history of the emergence of harakat in Arabic writing. The research method used is qualitative research method. The data collection technique used is by conducting a literature review on Indonesian literature and Arabic literature. The results of this study indicate that Arabic is a language that is included in the Semitic language and has many speakers in the world in Arabic there is a harakat, the harakat itself means moving, namely the harakat moves dead letters. The kinds of harakat are divided into 3 parts, namely al-Harakat al-Qashiroh, al-Harakat at-tawilah, and al- Harakat al-Ghoribah. The origin of harakat is due to the spread of Islam to various regions so that the use of the Qur'an is spreading. The initial originator of the harakat was Abu Aswad ad-Duali, then entered the sign on the letter which was then perfected by al-Khalil bin Ahmad al-Farahidi, namely giving the harakat with the inspiration of the hijaiyah letters.